Coping with basic military training - Teo, Dorothy Cheok Heng. (2008)
The majority of young male Singaporeans and permanent residents who reach the age of 18 to 23 years are conscripted for about two and half years to serve National Service in the Singapore Armed Forces. A review of research literature indicates that the transition from civilian to military life may be stressful for some, particularly during the first 10 weeks of Basic Military Training. The objectives of this study were to find out the factors that were related to the ability to cope with Basic Military Training, both in terms of psychological well being as well as in physical performance. The sample comprised of a Company of 200 recruits who underwent the enhanced Basic Military Training course. Measurements were made at three points of time; on the first day of enlistment, during the high training stress period, and during the low training stress period. The Esyenck Personality Scale, Ways of Coping Questionnaire, General Health Questionnaire, Personal Problems Checklist and Perceived Social Support Questionnaire were used. Results of the Individual Physical Proficiency Test and pass rates were obtained from the trainer. The data was analyzed using correlational analysis, one-way and multivariate analysis of variance, independent t-test and multiple regression analysis.